2005
DOI: 10.1007/s10888-005-9008-2
|View full text |Cite
|
Sign up to set email alerts
|

Safety segregation: The importance of gender, race, and ethnicity on workplace risk

Abstract: economic inequality, employment conditions, fatalities, hedonic equilibrium, non-fatal injuries, Oaxaca decomposition, occupational choice, standardized injury rates, workplace safety,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…An increase of the fraction of women (4.7 % for the years 1953-1989; 8.5% for 1990-1999; 10.3% for 2000-2005) was also observed on Everest (Huey et al, 2007). The values given for other time periods for the Nepalese Himalayas (10.2% females for the period 1970-2010; Westhoff et al, 2012) and Everest (7.8% females for the time period 1921-2006Firth et al, 2008) fit into this general trend.…”
Section: Human Factorsmentioning
confidence: 56%
“…An increase of the fraction of women (4.7 % for the years 1953-1989; 8.5% for 1990-1999; 10.3% for 2000-2005) was also observed on Everest (Huey et al, 2007). The values given for other time periods for the Nepalese Himalayas (10.2% females for the period 1970-2010; Westhoff et al, 2012) and Everest (7.8% females for the time period 1921-2006Firth et al, 2008) fit into this general trend.…”
Section: Human Factorsmentioning
confidence: 56%
“…Number of family members and marital status have been used in some studies as proxies for risk preferences (Leeth and Ruser, 2006;DeLeire and Levy, 2004). Size of the family and risk are expected to be negatively correlated.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…For instance, inequalities in lifetime levels of wealth -supposedly lower for immigrantsmay explain differences in willingness to bear risk, i.e., immigrants or ethnic minorities would be more likely to accept and to be employed in high-risk jobs (Robinson, 1984;Viscusi, 2003;Leeth and Ruser, 2006). Immigrants and non-immigrants might also differ in terms of market opportunities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in the United States -the country most widely studied (Ahonen and Benavides 2008), early studies found that immigrants generally endured lower work injury rates than natives (Berger andGabriel 1991, Hamermesh 1998). However, more recent studies suggest that immigrants, especially Hispanics, endure higher work injury rates than natives (Loh and Richardson 2004, Leeth and Ruser 2006, Orrenius and Zavodny 2009. The evidence for other nations is rather scarce and varies widely from country to country.…”
Section: Work Injuries and Fatalities By Nativity And Over The Econommentioning
confidence: 99%